(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
In this paper, we study and introduce the notion of -identification function which is a function from a topological space to another topological space and be two operators associative with respectively, then is called -identification function if and only if is onto and is -open set in if and only if is -open set in .